Enhancement of thermoelectric figure of merit in Bi2Se3 crystals through a necking process. (1st April 2015) - Gupta, Shashikant; Vijayan, N.; Krishna, Anuj; Thukral, Kanika; Maurya, K. K.; Muthiah, Saravanan; Dhar, Ajay; Singh, Budhendra; Bhagavannarayana, G.
<x xml:space="preserve">Abstract</x> The growth of good quality bulk single crystals of bismuth selenide by employing a high‐temperature vertical Bridgman technique with a specially designed ampoule having a provision for a necking process is reported. Several growth experiments were performed and reproducible results were obtained. The crystal structure and lattice dimensions were confirmed by powder X‐ray diffraction (PXRD), the bulk crystalline perfection was assessed using high‐resolution X‐ray diffractometry and the good bulk crystalline perfection with an indication of layered structure was confirmed. Transmission electron microscopy (TEM) was carried out for the grown single crystal and confirmed the layered structure. High‐resolution TEM (HRTEM) was also used to further assess the crystalline perfection. The direct measurement of d spacing obtained from HRTEM imaging was found to be in good agreement with the data obtained from PXRD. The thermal behavior was examined by differential scanning calorimetry and a sharp melting was found at 983 K, which revealed the purity of the bismuth selenide. The Seebeck coefficient and electrical and thermal conductivities were measured, and a thermoelectric figure of merit was calculated in order to assess the suitability of the crystal for thermoelectric applications such as refrigeration and portable power generation. Nanoindentation analysis was also performed for the first time.